Tensile and fatigue behaviour of glass fibre reinforced polyester composites - Jimit, Roy Hanson; Zakaria, Kamarul Ariffin; Bapokutty, Omar; Dhar Malingam, Sivakumar (Science Publishing Corporation Inc, 2018)
This document contains the formatting information for the papers presented at the International conference on “4th International Conference on Recent Advances in Automotive Engineering & Mobility Research (ReCAR IV)”. The conference would be held at Hotel Bangi-Putrajaya during August 8-10, 2017. Fibreglass composites are one of the materials that can be used in manufacturing of the vehicles part due to their excellent lightweight properties. Composite structures may undergone the fatigue failure when subjected to a certain numbers of cyclic loading, which is normally occurs below the ultimate strength of material. However, there still lack of studies on the effect of fibre orientations on the fatigue strength of glass fibre reinforced composites (GFRC). Therefore, the purpose of this study is to determine which orientation would have the highest fatigue strength. The fibre materials used in this study is unidirectional glass fibre with [0/90]°, [ ±45]° orientation and chopped strand mat (CSM). The composite is fabricated from glass fibre and polyester resin using a hand lay-up technique according to ASTM D3039 for tensile test and ASTM D3479 for fatigue test. The results were pre-sented in the form of S-N curve. The results show that the mechanical properties and fatigue behavior were significantly affected by the fibre orientation of the GFRC.